FRI0039 VISFATIN/PBEF in bone remodelling of rheumatoid arthritis. (23rd January 2014) - Krumbholz, G.; Junker, S.; Lehr, A.; Rickert, M.; Schett, G.; Rehart, S.; Müller-Ladner, U.; Neumann, E.
Abstract : Objectives: Rheumatoid arthritis (RA) is associated with increased production of adipocytokines, which are cytokine-like mediators. Increased levels of the adipokine visfatin were found in synovial fluid and tissue of RA patients. Moreover, visfatin promotes the synthesis of pro-inflammatory and matrix-degrading effector molecules in RA synovial fibroblasts. However, the role of visfatin in bone remodelling of RA is unclear. In this study, we focussed on visfatin and its influence on RA osteoblast activity and differentiation as well as on its immunomodulatory properties on RA osteoblasts. Methods: For expression analysis of visfatin, bone tissue obtained from RA patients during joint replacement surgery, was analyzed. Serial sections of decalcified and deparaffinised bone tissue were used to identify the expression sites of visfatin in articular remodelling. (Immuno)histochemistry was performed by using anti-visfatin and anti human ALP (alkaline phosphatase) antibodies in addition to Masson- and TRAP-staining. Human osteoblasts isolated from bone tissue of RA patients were stimulated with visfatin. Visfatin-mediated effects on human osteoblasts were analyzed on the transcriptional and translational level using quantitative realtime polymerase chain reaction (qRT-PCR) and immunoassays. Furthermore, the cells were stimulated with the pro-inflammatory cytokine IL-1β and gene expression of visfatin was examined by qRT-PCR. Results: Immunohistochemical staining of RA bone tissue showed a co-localization of visfatin with key cells of bone remodelling (osteoblasts, osteoclasts). Stimulation with visfatin induced the secretion of pro-inflammatory cytokines (e.g. IL-6: 5-fold increase; IL-8: up to 100-fold) in RA osteoblasts. Additionally, quantitative realtime PCR showed several genes being differentially expressed in osteoblasts after stimulation with Visfatin ( e.g . alkaline phosphatase, osteocalcin, OPG). Furthermore, the stimulation with IL-1β led to a 5-fold increase of Visfatin gene expression in RA osteoblasts. Conclusions: The results of the present study indicate that visfatin influences the activity as well as the differentiaton of human osteoblasts in RA by modulating the expression of genes being involved in matrix production and osteoblast phenotype development. These results, together with the finding of increased visfatin expression in osteoblasts after IL-1β treatment, support the idea of visfatin affecting bone metabolism in RA. Acknowledgement: Funded by the German Research Society (SPP1468, IMMUNOBONE, NE1174/6-1). Disclosure of Interest: None Declared